STRATEGI PEMASARAN BISNIS FASTFOOD PALUPI CULINARY DALAM MENINGKATKAN PENJUALAN (Studi Penelitian di Palupi Culinary Kota Bengkulu) - Sri Ekowati; Nabila Saufira (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2023)
This type of research is field research with a qualitative descriptive approach. The results showed that the internal factor score of Palupi Culinary's strengths and weaknesses has a total score of 3.37, because the total score is close to 4.00, which means that Palupi Culinary has strong internal factors. In addition, external factors, opportunities and threats, Palupi Culinary has a total score of 3.014, because the total score is close to 4.00, this indicates that Palupi Culinary responds to opportunities in an extraordinary way and avoids threats in its industrial market. Palupi Culinary's position is in quadrant 1 with internal factor coordinates +0.60, and external factor +0.20. This means that Palupi Culinary is in a very favorable situation. Palupi Culinary has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy (growth oriented strategy). Palupi Culinary carries out a growth strategy Growth strategy which is the growth of the company itself, through vertical integration (cell 1), which is an activity to expand the market by maximizing promotions in marketing and building branches in other locations.